Batik Kontemporer Majapahitan Sebagai Daya Dukung Cultural Tourism di Kota Mojokerto - Muhammad Iqbal Maulana; Rahmad Saiful Ramadhani; Ratnaningrum Z.D (Institut Nalanda, 2024)
Indonesia is a country that produces cultural tourism in various specific regions, one of which supports cultural tourism is the development of Majapahitan contemporary batik and its potential to support cultural tourism in the city of Mojokerto. Majapahitan Contemporary Batik is a modern adaptation of traditional batik designs originating from Majapahit culture. This research aims to determine the characteristics of contemporary Majapahitan batik, explore its creative development, and examine its role in supporting cultural tourism in the city of Mojokerto. The research methods used were field observation, in-depth interviews with parties involved in the Majapahitan contemporary batik industry and documentation to take photos while in the field. The research results show that contemporary Majapahitan batik has unique characteristics, using traditional Majapahit motifs such as bricks, gates, walls and Surya Majapahit combined with a modern touch. The creative process in development includes innovation in coloring techniques, application of patterns, and product diversification. Majapahitan contemporary batik has proven to play an important role as an attraction for tourists to get to know the local culture of Mojokerto and can support the development of the creative economy and cultural tourism industry in the area. Majapahitan contemporary batik has great potential to be developed as a premium product in the city of Mojokerto and become a supporting force in the development of cultural tourism. Efforts to preserve, innovate and promote Majapahitan contemporary batik must continue to be carried out to increase competitiveness and contribute to the cultural tourism industry in Mojokerto City.